PENGARUH PENGUKURAN RETURN ON ASSET, RETURN ON EQUITY, EARNING PER SHARE, DAN ECONOMIC VALUE ADDED TERHADAP MARKET VALUE ADDED - Mizan, Enniyatul (JURNAL AKUNTANSI DAN INVESTASI, 2018)
The purpose of this study is to determine whether each change in value of return on assets, return on equity, earnings per share, and economic value added will be followed by a pattern of changes in the value of the market value added. This research is a type of quantitative descriptive research with statistical tests. The population used by the researcher is a manufacturing company listed on the Indonesia Stock Exchange (IDX) period 2013-2015 as many as 131 companies. The technique used in determining the sample of this study is purposive sampling. The data analysis technique used in this study is multiple linear regression analysis because to find out whether there is a significant influence between the independent variables on the dependent variable with the help of SPSS for windows version 21. Test results show that return on assets, return on equity and earnings per share no significant effect on market value added, while economic value added significant effect on market value added. While based on the F test it can be concluded that the independent variables namely return on assets, return on equity, earnings per share and economic value added affect simultaneously on the market value added. This shows that the independent variables are jointly able to explain the dependent variable.